The treatment of spleen injuries: a retrospective study - Dehli, Trond; Bågenholm, Anna; Trasti, Nora; Monsen, Svein Arne; Bartnes, Kristian (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2015)
Published version. Source at http://doi.org/10.1186/s13049-015-0163-6 . Background Hemorrhage after blunt trauma is a major contributor to death after trauma. In the abdomen, an injured spleen is the most frequent cause of major bleeding. Splenectomy is historically the treatment of choice. In 2007, non-operative management (NOM) with splenic artery embolization (SAE) was introduced in our institution. The indication for SAE is hemodynamically stable patients with extravasation of contrast, or grade 3–5 spleen injury according to the Abbreviated Organ Injury Scale 2005, Update 2008. We wanted to examine if the introduction of SAE increased the rate of salvaged spleens in our trauma center. Method All patients discharged with the diagnosis of splenic injury in the period 01.01.2000 – 31.12.2013 from the University Hospital of North Norway Tromsø were included in the study. Patients admitted for rehabilitation purposes or with an iatrogenic injury were excluded. Results A total of 109 patients were included in the study. In the period 2000-7, 20 of 52 patients were splenectomized. During 2007-13, there were 6 splenectomies and 24 SAE among 57 patients. The reduction in splenectomies is significant (p < 0.001). There is an increase in the rate of treated patients (splenectomy and SAE) from 38 to 53 % in the two time periods, but not significantly (p = 0.65). Conclusion The rate of salvaged spleens has increased after the introduction of SAE in our center.